Encountering the sovereign other : indigenous science fiction - Spiers, Miriam C. Brown (American Indian studies series (East Lansing, Mich.), 2021)
"Demonstrating how Indigenous science fiction expands the boundaries of the genre while reinforcing the relevance of Native knowledge, author Miriam C. Brown Spiers analyzes four novels: William Sanders's The Ballad of Billy Badass and the Rose of Turkestan, Stephen Graham Jones's It Came From Del Rio, D. L. Birchfield's Field of Honor, and Blake M. Hausman's Riding the Trail of Tears"--